Peer-to-Peer Permissionless Consensus via Reputation - Sant’Anna, Francisco; Bosisio, Fabio; Pires, Lucas (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2023)
Public Internet forums suffer from excess and abuse, such as SPAM and fake news. Centralized platforms employ filtering and anti-abuse policies, but imply full trust from users. We propose a permissionless Sybil-resistant peer-to-peer protocol for content sharing. Our main contribution is a reputation system that moderates content and, at the same time, delivers network consensus. We can trace a parallel with Bitcoin as follows: consolidated posts create reputation (vs proof-of-work), likes and dislikes transfer reputation (vs transactions), and aggregate reputation determines consensus (vs longest chain). The reputation mechanism depends exclusively on the human authoring ability (proof-of-authoring), which is slow and scarce, thus suitable to establish consensus.